Anti-cancer activity of guggulsterone by modulating apoptotic markers: a systematic review and meta-analysis - Gupta, Meenakshi; Singh, Deepti; Rastogi, Shruti; Siddique, Hifzur R.; Al-Dayan, Noura; Ahmad, Ajaz; Sikander, Mohammad; Sarwat, Maryam (Frontiers in Pharmacology, 2023)
Background: Guggulsterone, an effective phytosterol from Commiphora wightii, is a traditional medicinal plant of Ayurveda and Unani systems of medicine. It exhibits anti-inflammatory, analgesic, antibacterial, anti-septic and anticancer activities. In this article, the anticancer effect of Guggulsterone was determined and summarized. Methods: Using 7 databases (PubMed, PMC, Google Scholar, Science Direct, Scopus, Cochrane and Ctri.gov), the literature search yielded 55,280 studies. 40 articles were included in systematic review, 23 articles were selected for meta‐analysis.The selected articles covered wide range of cancerous cell lines. The reliability of the selected studies was assessed using ToxRTool. Results: Guggulsterone significantly affected pancreatic cancer (MiaPaCa-2, Panc-1, PC-Sw, CD18/HPAF, Capan1, PC-3), hepatocellular carcinoma (Hep3B, HepG2, PLC/PRF/5R), head and neck squamous cell carcinoma (SCC4, UM-22b, 1483), cholangiocarcinoma (HuCC-T1, RBE, Sk-ChA-1, Mz-ChA-1) and oesophageal adenocarcinoma (CP-18821, OE19), prostrate cancer (PC-3), colon cancer (HT-29), breast cancer (MCF7/DOX), gut derived adenocarcinoma (Bic-1), gastric cancer (SGC-7901), colorectal cancer (HCT116), bladder cancer (T24, TSGH8301), glioblastoma (A172, U87MG, T98G), histiocytic leukemia (U937), acute myeloid leukemia (HL60, U937) and non-small cell lung cancer (A549, H1975) by inducing apoptotic pathways, inhibiting cell proliferation, and regulating the expression of genes involved in apoptosis. Guggulsterone inhibits and suppresses the proliferation of an extensive range of cancer cells by decreasing intrinsic mitochondrial apoptosis, regulating NF-kB/STAT3/β-Catenin/PI3K/Akt/CHOP pathway, and inhibiting angiogenesis. Furthermore, Guggulsterone reduces the production of inflammatory markers. 23 studies were selected for meta-analysis following the PRISMA statements. Fixed effect model was used for reporting the odds ratio. The primary endpoint was percentage apoptosis. 11 of 23 studies reported the apoptotic effect at t=24h and pooled odds ratio was 3.984 (CI 3.263 to 4.865, p<0.001). 12 studies used Guggulsterone for t>24h and the odds ratio was 11.171 (CI 9.148 to 13.643, 95% CI, p<0.001). The sub-group analysis based on cancer type, Guggulsterone dose, and treatment effects. Significant alterations in the level of apoptotic markers were reported by Guggulsterone treatment. Conclusion: Guggulsterone showed apoptotic effects against various cancer types. Further investigation of its pharmacological activity and mechanism of action should be conducted. In vivo experiments and clinical trials are required to confirm the anticancer activity.